Metabolomics‐related nutrient patterns at seroconversion and risk of progression to type 1 diabetes. Issue 7 (9th August 2020) - Johnson, Randi K.; Vanderlinden, Lauren A.; DeFelice, Brian C.; Uusitalo, Ulla; Seifert, Jennifer; Fan, Sili; Crume, Tessa; Fiehn, Oliver; Rewers, Marian; Kechris, Katerina; Norris, Jill M.
Abstract: Objective: Our aim was to elucidate the role of diet in type 1 diabetes (T1D) by examining combinations of nutrient intake in the progression from islet autoimmunity (IA) to T1D. Methods: We measured 2457 metabolites and dietary intake at the time of seroconversion in 132 IA‐positive children in the prospective Diabetes Autoimmunity Study in the Young. IA was defined as the first of two consecutive visits positive for at least one autoantibody (insulin, GAD, IA‐2, or ZnT8). By December 2018, 40 children progressed to T1D. Intakes of 38 nutrients were estimated from semiquantitative food frequency questionnaires. We tested the association of each metabolite with progression to T1D using multivariable Cox regression. Nutrient patterns that best explained variation in candidate metabolites were identified using reduced rank regression (RRR), and their association with progression to T1D was tested using Cox regression adjusting for age at seroconversion and high‐risk HLA genotype. Results: In stepwise selection, 22 nutrients significantly predicted at least two of the 13 most significant metabolites associated with progression to T1D, and were included in RRR. A nutrient pattern corresponding to intake lower in linoleic acid, niacin, and riboflavin, and higher in total sugars, explained 18% of metabolite variability. Children scoring higher on this metabolite‐related nutrient pattern at seroconversion had increased risk for progressing to T1D (HR = 3.17, 95%CI = 1.42‐7.05). Conclusions: Combinations of nutrient intake reflecting candidate metabolites are associated with increased risk of T1D, and may help focus dietary prevention efforts.